RGB-Guided Depth Map Recovery by Two-Stage Coarse-to-fine Dense CRF Models - Wang, Haotian (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2023)
Depth maps generally suffer from large erroneous areas even in public RGB-Depth datasets. Existing learning-based depth recovery methods are limited by insufficient high-quality datasets and optimization-based methods generally depend on local contexts not to effectively correct large erroneous areas. This paper develops an RGB-guided depth map recovery method based on the fully connected conditional random field (dense CRF) model to jointly utilize local and global contexts of depth maps and RGB images. A high-quality depth map is inferred by maximizing its probability conditioned upon a low-quality depth map and a reference RGB image based on the dense CRF model. The optimization function is composed of redesigned unary and pairwise components, which constraint local structure and global structure of depth map, respectively, with the guidance of RGB image. In addition, the texture-copy artifacts problem is handled by two-stage dense CRF models in a coarse-to-fine way. A coarse depth map is first recovered by embedding RGB image in a dense CRF model in unit of 3×3 blocks. It is refined afterward by embedding RGB image in another model in unit of individual pixels and restricting the model mainly work in discontinued regions. Extensive experiments on six datasets verify that the proposed method considerably outperforms a dozen of baseline methods in correcting erroneous areas and diminishing texture-copy artifacts of depth maps